The NICE Evidence Standards Framework for digital health and care technologies - developing and maintaining an innovative evidence framework with global impact - Unsworth, H; Dillon, B; Collinson, L; Powell, JA; Salmon, M; Oladapo, T; Ayiku, L; Shield, G; Holden, J; Patel, N; Campbell, M; Greaves, F; et al. (SAGE Publications, 2021)
Objective: In 2018, the UK National Institute for Health and Care Excellence (NICE), in partnership with Public Health England, NHS England, NHS Improvement and others, developed an evidence standards framework (ESF) for digital health and care technologies (DHTs). The ESF was designed to provide a standardised approach to guide developers and commissioners on the levels of evidence needed for the clinical and economic evaluation of DHTs by health and care systems.